2018
DOI: 10.5851/kosfa.2018.e46
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Lesion Incidence in Pork Carcass Using Transdermal Needle-free Injection of Foot-and-Mouth Disease Vaccine

Abstract: Foot-and-mouth disease (FMD) is an infectious disease affecting pigs. The control of FMD in swine husbandry is very important because its outbreak results in a vast economic loss. FMD vaccination has effectively controlled FMD; however, it results in economic loss associated with the incidence of lesions in the pork meat at the injection site. The objective of this study was to investigate the effects of transdermal needle-free injection (NFI) of the FMD vaccine on the incidence of lesions at the injection sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Besides representing a substantial economic loss, the presence of tissue damage at the site of injection in pig carcasses is an indicator that pain occurred. Contrary to Houser et al [ 21 ] who did not report a significant difference in carcass lesions between vaccination methods, carcass defects (such as granuloma, abscess, and fibrosis) resulting from intramuscular injections of vaccines have been reported in some studies [ 24 , 25 ]. Needle-free injections might be expected to prevent possible tissue damage and bacterial contamination caused by needles.…”
Section: Introductionmentioning
confidence: 87%
“…Besides representing a substantial economic loss, the presence of tissue damage at the site of injection in pig carcasses is an indicator that pain occurred. Contrary to Houser et al [ 21 ] who did not report a significant difference in carcass lesions between vaccination methods, carcass defects (such as granuloma, abscess, and fibrosis) resulting from intramuscular injections of vaccines have been reported in some studies [ 24 , 25 ]. Needle-free injections might be expected to prevent possible tissue damage and bacterial contamination caused by needles.…”
Section: Introductionmentioning
confidence: 87%
“…The incident rate of lesions on the pork butt (vaccination site) was 21.70% in the control group (Figure 1). This value is higher than 19.17% of a previous study [11]. In the present study, the FMD vaccine was injected in the neck, while the [23] and three types of hypothetical farm size are assumed: farms with 100, 500, and 1,000 sows.…”
Section: Resultsmentioning
confidence: 91%
“…Cho et al (2020) Asian-Australas J Anim Sci 33:634-639 vaccination site was the ham in the previous study [11]. Ko et al [2] found that the incident rate of lesions differed with different sites of injection, and it was higher in the neck than in pork ham.…”
mentioning
confidence: 90%
See 2 more Smart Citations